2015
DOI: 10.1371/journal.pone.0133350
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Chemical Coding of the Inner and Outer Submucous Plexus in the Colon of Piglets

Abstract: In the porcine colon, the submucous plexus is divided into an inner submucous plexus (ISP) on the epithelial side and an outer submucous plexus (OSP) on the circular muscle side. Although both plexuses are probably involved in the regulation of epithelial functions, they might differ in function and neurochemical coding according to their localization. Therefore, we examined expression and co-localization of different neurotransmitters and neuronal markers in both plexuses as well as in neuronal fibres. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 61 publications
(71 reference statements)
4
21
2
Order By: Relevance
“…Then, the following primary antibodies were used: rabbit polyclonal anti-P2X2 antibody (ab48864, RRID: AB_881833, Abcam, diluted 1:400), mouse monoclonal anti-Calbindin D-28k (CB300, RRID: AB_10000347, Swant® Swiss Antibodies, diluted 1:2500), Chicken polyclonal anti-Neurofilament 200 (NFH, RRID: AB: AB_2313552, Aves Labs, INC., diluted 1:10000), Chicken polyclonal anti-TH (THY, RRID: AB_100113440, Aves Labs, INC., diluted 1:100), Rat monoclonal Anti-Substance P (SP, ab7340, RRID: AB_305866, Abcam, diluted 1:1000) and rabbit polyclonal Anti-Neuropeptide Y (22940, RRID: AB_2307354, ImmunoStar Inc, diluted 1:1000). The specificity of the primary antibodies has been published elsewhere 71 75 . For slices treated with mouse monoclonal CB300 antibody, an additional incubation with unconjugated Goat anti-mouse Fab fragment (10 ug/ml) in blocking solution was applied for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the following primary antibodies were used: rabbit polyclonal anti-P2X2 antibody (ab48864, RRID: AB_881833, Abcam, diluted 1:400), mouse monoclonal anti-Calbindin D-28k (CB300, RRID: AB_10000347, Swant® Swiss Antibodies, diluted 1:2500), Chicken polyclonal anti-Neurofilament 200 (NFH, RRID: AB: AB_2313552, Aves Labs, INC., diluted 1:10000), Chicken polyclonal anti-TH (THY, RRID: AB_100113440, Aves Labs, INC., diluted 1:100), Rat monoclonal Anti-Substance P (SP, ab7340, RRID: AB_305866, Abcam, diluted 1:1000) and rabbit polyclonal Anti-Neuropeptide Y (22940, RRID: AB_2307354, ImmunoStar Inc, diluted 1:1000). The specificity of the primary antibodies has been published elsewhere 71 75 . For slices treated with mouse monoclonal CB300 antibody, an additional incubation with unconjugated Goat anti-mouse Fab fragment (10 ug/ml) in blocking solution was applied for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…The neurons not preferentially approached by capillaries, among them the morphologically striking, nondendritic type II neurons, were shown to be nonnitrergic but cholinergic [Brehmer et al, 2004;Wolf et al, 2007]. It can be assumed that additional neuroactive substances are colocalized with nNOS in the respective myenteric and submucosal type III neurons [Timmermans et al, 2001;Kapp et al, 2006;Wojtkiewicz et al, 2012;Petto et al, 2015]. The further deciphering of the chemical code of porcine type III neurons including quantitative data will be performed in a future project.…”
Section: Enteric Neurons Approached By Capillariesmentioning
confidence: 98%
“…With this study, we confirmed our hypothesis on the presence of MEN in the SMP of the porcine and human colon. So far, studies on SMP of the pig focused on the electrophysiology of neurons as revealed by intracellular recordings 37 or the expression of transmitter and neuropeptides 8,[38][39][40][41][42] . Although the pig is frequently advocated as a model for humans [31][32][33][34][35][36] , there are surprisingly few original studies which back up this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining of submucosal MEN of the porcine proximal and distal colon for ChAT and SP immunoreactivity showed no significant differences between the intestinal regions investigated regardless of whether tensile or compressive forces were applied. A study performed in the porcine colon revealed that the proportion of enteric ISMP neurons immunoreactive for ChAT was 43%, 66% of those also expressed SP, and no neurons solely expressed SP 8 . Our immunohistochemical staining of MEN mainly reflected these data, and this agrees with our previous results in the guinea pig ileum and stomach, where MEN also did not show a particular neurochemical code 14 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation